2012
DOI: 10.1016/j.ppnp.2011.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Variational approach to Yang–Mills theory with non-Gaussian wave functionals

Abstract: A general method for treating non-Gaussian wave functionals in quantum field theory is presented and applied to the Hamiltonian approach to Yang-Mills theory in Coulomb gauge in order to include a three-gluon kernel in the exponential of the vacuum wave functional. The three-gluon vertex is calculated using the propagators found in the variational approach with a Gaussian trial wave functional as input.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…On the other hand, interestingly enough, in Refs. [24][25][26], pure Yang-Mills theories have been investigated within the Schrödinger representation in the Coulomb gauge. These authors, by using vacuum functionals that are strongly peaked at the Gribov horizon, showed that the vacuum functional becomes field independent in the infrared consistent with a stochastic vacuum at large distances.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, interestingly enough, in Refs. [24][25][26], pure Yang-Mills theories have been investigated within the Schrödinger representation in the Coulomb gauge. These authors, by using vacuum functionals that are strongly peaked at the Gribov horizon, showed that the vacuum functional becomes field independent in the infrared consistent with a stochastic vacuum at large distances.…”
Section: Introductionmentioning
confidence: 99%